Mengintegrasikan Gerakan Sholat Sebagai Praktik Preventif Gangguan Muskuloskeletal: Sebuah Pendekatan Fenomenologi Terhadap Pengalaman Individu - Setianto, Gigih; Setyawan, M. Ghilang Maulud; Risdiani, Risdiani (Yayasan Jompa Research and Development, 2025)
Musculoskeletal disorders (MSDs) are health conditions that frequently disrupt quality of life and productivity. Previous studies have shown that physical activities such as stretching and physical therapy can help prevent these disorders. The movements performed during shalat (Islamic prayer), a routine act of worship for Muslims, share biomechanical similarities with physical exercise. However, there is still limited exploration of individuals’ subjective experiences in integrating shalat movements as a preventive measure against MSDs. This study aims to explore the meanings and perceptions of individuals regarding the integration of shalat movements into daily life to maintain musculoskeletal health. A qualitative approach with a phenomenological method was employed in this study. Data were collected through in-depth interviews, participatory observations, and documentation, and then analyzed thematically. The findings reveal three main themes: the dual meaning of shalat movements (as worship and as therapy), postural awareness during shalat, and the adaptation and consistency of shalat movements in maintaining flexibility and reducing pain complaints. The study concludes that performing shalat movements correctly and consistently can serve as a promotive and preventive effort against musculoskeletal disorders. These findings provide a foundation for integrating religious values into public health education programs.